Physico-Chemical Properties And Antioxidant Activities of Rhodomytus tomentosa syrup - Widia Dara; Nurhamidah Nurhamidah (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2021)
Antioxidants are natural compounds found in many fruits, as well as in Rhodomyrtus tomentosa. The research, Rhodomyrtus tomentosa will be processed in form of syrup. The results of the organoleptic test of syrup ranged from like to very like by panelists. Determine the physical and chemical properties on syrup Rhodomyrtus tomentosa were acidity value is 4,41, total acid is 0,003%, total dissolved solids 23,74oBrix and sugar level of syrup is 21%. The results of Vitamin C content analysis of 1.25 mg / 100 g. The syrup contains Fe 0.525 mg / L and Cu 0.220 mg / L. In the Rhodomyrtus tomentosa syrup there is no lead (Pb), cadmium (Cd), Mercuri (Hg), Arsenic (As) and Stanum (Sn) metal. The content of antioxidant activity sirup is 10.31 %.